Active degassing across the Maltese Islands (Mediterranean Sea) and implications for its neotectonics. (June 2019) - Micallef, Aaron; Spatola, Daniele; Caracausi, Antonio; Italiano, Francesco; Barreca, Giovanni; D'Amico, Sebastiano; Petronio, Lorenzo; Coren, Franco; Facchin, Lorenzo; Blanos, Rita; Pavan, Alessandro; Paganini, Paolo; et al.
Abstract: The Maltese Islands, located in the central Mediterranean Sea, are intersected by two normal fault systems associated with continental rifting to the south. Due to a lack of evidence for offshore displacement and insignificant historical seismicity, the systems are thought to be inactive and the rift-related deformation is believed to have ceased. In this study we integrate aerial, marine and onshore geological, geophysical and geochemical data from the Maltese Islands to demonstrate that the majority of faults offshore the archipelago underwent extensional to transtensional deformation during the last 20 ka. We also document an active fluid flow system responsible for degassing of CH4 and CO2 . The gases migrate through carbonate bedrock and overlying sedimentary layers via focused pathways, such as faults and pipe structures, and possibly via diffuse pathways, such as fractures. Where the gases seep offshore, they form pockmarks and rise through the water column into the atmosphere. Gas migration and seepage implies that the onshore and offshore faults systems are permeable and that they were active recently and simultaneously. The latter can be explained by a transtensional system involving two right-stepping, right-lateral NW-SE trending faults, either binding a pull-apart basin between the islands of Malta and Gozo or associated with minor connecting antitethic structures. Such a configuration may be responsible for the generation or reactivation of faults onshore and offshore the Maltese Islands, and fits into the modern divergent strain-stress regime inferred from geodetic data. Highlights: The majority of faults offshore the Maltese Islands underwent deformation in last 20 ka. Active degassing of CH4 and CO2 occurs onshore and offshore the Maltese Islands. A transtensional system with two right-lateral faults can explain these observations. This fits into the divergent strain-stress regime inferred from geodetic data.